2017
DOI: 10.1007/s00380-017-1086-0
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular end-diastolic dimension and septal e′ are predictors of cardiac index at rest, while tricuspid annular plane systolic excursion is a predictor of peak oxygen uptake in patients with pulmonary hypertension

Abstract: Little is known regarding a correlation of hemodynamics at rest or exercise capacity with echocardiographic parameters in patients with pulmonary hypertension (PH). To clarify these potential correlations, we performed transthoracic echocardiography, right heart catheterization, and cardiopulmonary exercise testing in 53 patients with pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH). Left ventricular end-diastolic dimension (LVDd), early diastolic velocity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The function of left ventricular is below average in most patients with hemodialysis, in which LVDd is considered as a predictor of mortality (Inoue, Ogawa, Iwabuchi, Otsuka, & Nitta, 2012). LVEDd, as an important predictor of cardiac index, is exhibited in high levels in children with acute myocarditis, which is closely associated with adverse outcomes (Kim et al, 2017;Nakano et al, 2018). In addition to LVED being highly exhibited in children with acute myocarditis, evaluation of left ventricular systolic function is usually conducted by measurement of FS and ejection with left ventricular dysfunction (Yamaguchi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The function of left ventricular is below average in most patients with hemodialysis, in which LVDd is considered as a predictor of mortality (Inoue, Ogawa, Iwabuchi, Otsuka, & Nitta, 2012). LVEDd, as an important predictor of cardiac index, is exhibited in high levels in children with acute myocarditis, which is closely associated with adverse outcomes (Kim et al, 2017;Nakano et al, 2018). In addition to LVED being highly exhibited in children with acute myocarditis, evaluation of left ventricular systolic function is usually conducted by measurement of FS and ejection with left ventricular dysfunction (Yamaguchi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A significant correlation was previously found between NT-proBNP and TAPSE in 60 patients with chronic heart failure ( 43 ). Furthermore, Nakano et al observed a significant positive correlation between TAPSE and cardiac index in patients ( 44 ).…”
Section: Discussionmentioning
confidence: 97%
“…Several other (pediatric and adult) studies have indicated that echocardiographic parameters for the left side of the heart offer prognostic information on PAH (9,23,24), although most of the previous studies have focused on anatomic and functional variables for the right side of the heart (8,10,17,(25)(26)(27)(28). In a systematic review and meta-analysis of prognostic factors in pediatric PAH, Ploegstra et al identified nine echocardiographic parameters where a single measurement was associated with length of survival in children, all of which were related to the function of the right side of the heart (26).…”
Section: Discussionmentioning
confidence: 99%